Implementasi Gerakan Literasi Sekolah di SD Negeri 48/I Penerokan - Risdaliani Risdaliani; Diana Ayu Puspita Sari; Muhammad Ilham; Syahrial Syahrial; Silvina Noviyanti (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2022)
This research discusses about the form of literacy implementation at SDN 48/I Penerokan. Literacy is a person's language skills (listening, speaking, reading, and writing). According to the national literacy movement, there are six kinds of basic literacy that students must possess, namely: numeracy literacy, scientific literacy, financial literacy, cultural literacy and digital literacy. This study uses a qualitative research with descriptive method, to describe the activities of teachers and students in the implementation of literacy education at SDN 48/I Penerokan. This study shows that the implementation of literacy education can provide a positive attitude to increase students' abilities and motivate. The problem faced by SDN 48/I Penerokan in the GLS is the low interest in reading in students. With some refraction within a class such as reading 15 minutes before the learning starts while outside ization is a library visit and a reading corner helps students increase student interest.